Parametric Optimization for Fatigue Life of 6061-T6 Aluminum Thin Sheets Processed with High-Speed Laser Shock Peening - Khudair, Ali Mohammed; Hussein, Furat I. (Iraqi Journal of Laser, 2021)
Abstract: Aluminum alloys grade 6061-T6 are characterized by their excellent properties and processing characteristics which make them ideal for varieties of industrial applications under cyclic loading, aluminum alloys show less fatigue life than steel alloys of similar strength. In the current study, a nanosecond fiber laser of maximum pulse energy up to 9.9 mJ was used to apply laser shock peening process (LSP) on aluminum thin sheets to introduce residual stresses in order to enhance fatigue life under cyclic loading Box-Behnken design (BBD) based on the design of experiments (DOE) was employed in this study for experimental design data analysis, model building and optimization The effect of working parameters spot size (ω), scanning speed (v) and pulse repetition rate (PRR) at three levels on the fatigue life expressed by the number of cycles (noc) were investigated The experimental results show an exclusive and significant percentage increase in the fatigue life of 505.25% and 477.81% when the ω= 0.04 mm and PRR= 22.5 kHz for two scanning speeds 200 mm/s and 500 mm/s respectively The optimized data extracted from the built model suggest a number of input parameters sets to enhance the performance of the process.